Alienação parental: uma análise sociojurídica da proteção à infância a sua aplicação no município de Maceió - Gomes, Cristina Maria Nascimento (2013)
The present dissertation has the main goal to solve the problems related with the familial breast violating children's rights, parental alienation, which only in 2010 was regulated by Law 12,318 in Brazil. Initially, this pathological social fact studies will be presented with the help of psychiatrist Richard Gardner. Then, emphasis will be given to the historical aspect of child protection, listing the major international and national legal instruments that protect children, tracing the evolution of the treatment given to the children as a subject of law framework. There will be a focus on Brazilian performance through specific legislation within this theme, conducting a detailed search of the law on the implementation and protection of basic rights of the child to preserve his training healthy. As a contribution to the positioning and display of law enforcement at the local level, quantitative data are listed in the first year of the law of alienation-August 2010 to August 2011 - obtained through research in family courts in the city of Maceió. Will also bring results concerning qualitative empirical research conducted through interviews and questionnaires answered by operators of the right child (prosecutors, judges, psychologists and social workers). Finally, it will be demonstrated the leading role played by NGOs from around the world to combat this practice of clarify some multidisciplinary proposals as joint custody and mediation, to avoid the problem is to install and desestruture family. As noted work is organized demonstrating in detail that there are legal instruments that protect the child, pointing to the local situation and proposing harmonic means of avoiding the installation of parental alienation in the family environment.